Spontaneous Reduction Finding: Magnetic Resonance Imaging Evaluation of Segmental Instability in Spondylolisthesis - Chung, Jae Yoon (Korean Society of Spine Surgery, 2012)
STUDY DESIGN: Retrospective chart review. PURPOSE: To assess whether spontaneous reduction of spondylolisthesis, as seen on magnetic resonance imaging (MRI), is related to the degree of segmental instability and low back pain. OVERVIEW OF LITERATURE: The flexion-extension radiographs obtained in the sagittal plane are frequently used when segmental instability of spondylolisthesis is evaluated. METHODS: We retrospectively reviewed 137 patients and measured the differences of the percentage of sagittal translation and sagittal angulation to determine the segmental instability between the flexion and extension radiographs, and the spontaneous reduction on MRI. We then compared the degrees of segmental instability and the degrees of spontaneous reduction. To assess the effect of low back pain on segmental motion in regards to the flexion-extension radiographs, we compared the preoperative visual analogue scales (VAS) score for low back pain between the more and the less spontaneous reduction groups. RESULTS: The mean degree of spontaneous reduction was 5.2%. A statistically significant correlation was found between the sagittal translation on the flexion-extension radiographs and the degree of spontaneous reduction (r = 0.557, p < 0.001) and between the sagittal angulation on the flexion-extension radiographs and the degree of spontaneous reduction (r = 0.215, p = 0.012). The preoperative VAS scores for low back pain of the more spontaneous reduction group and the less spontaneous reduction group were 4.6 and 3.6 points, respectively, and this difference was statistically significant (p = 0.002). CONCLUSIONS: Spontaneous reduction of spondylolisthesis on MRI was found to be closely related to segmental instability, and the degree of spontaneous reduction seen on MRI could be useful for the evaluation of segmental instability in patients with spondylolisthesis, especially with severe low back pain.